2019
DOI: 10.25186/cs.v14i2.1563
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic in the Spatial and Temporal Distribution in the Quality of the Beverage in Conilon Coffee

Abstract: <p>The objective in this study was to evaluate the spatial and temporal variability of the beverage quality by applying the fuzzy classification in the final global sensory analysis, for Coffea canephora Pierre ex A. Froehner, in two consecutive harvests. The studied variables were: fragrance (aroma), flavor, bitterness (sweetness), set, balance, cleaning, aftertaste, mouth feel, uniformity, salinity (acidity) and drink (global note). To the average overall scores of the drinks obtained on the cup-tastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…These results indicate that both the effects of genotypes (clones) and the effect of the GxE interaction are important for the expression of the beverage quality. Significant effects of the genotype × environment interaction in coffee growing were also reported in other studies (Barbosa et al, 2012;Borém et al, 2019;Laviola et al, 2007;Fonseca et al, 2019;Moura et al, 2017).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These results indicate that both the effects of genotypes (clones) and the effect of the GxE interaction are important for the expression of the beverage quality. Significant effects of the genotype × environment interaction in coffee growing were also reported in other studies (Barbosa et al, 2012;Borém et al, 2019;Laviola et al, 2007;Fonseca et al, 2019;Moura et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…The two scores are then added to determine the result of the bitterness/sweetness relationship (SCA, 2013); in this study, sweetness exceeded bitterness. The scores of all the attributes of the sensory profile of the clones were higher than the values observed by Fonseca et al (2019), with a mean score of 75.58 points in the 2016/2017 crop season in the state of Espírito Santo.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Ribeiro et al (2014) and Souza et al (2018) select the overall average score (OS) of 68.4 and 66.5, respectively, for clonal conilon coffee, classified as good quality coffee and not specific for the type of sieve in the studies. Fonseca et al (2019) found OS of 75.4 for seminal conilon coffee produced at high altitude, classified as very good coffee, separated in sieves 13.…”
Section: Resultsmentioning
confidence: 98%
“…The quality of the beverage the conilon coffee beans (Coffea canephora) has been the object of several studies due to the demanding domestic and international markets. The market demand for the consumption better quality coffee is leading farmers to improve production processes in order to achieve higher results in the final global score of beverages in the hedonic scale (Fonseca et al, 2019). One of the methods for assess the quality of the beverage is a sensory analysis, which depends on the sensitivity and tasting experience of accredited tasters based on specific protocols.…”
Section: Introductionmentioning
confidence: 99%